EXPRESSION OF SCAVENGER RECEPTOR AND CELL ADHESION MOLECULE GENES IN HUMAN ENDOTHELIAL CELLS EXPOSED TO MINERAL-ORGANIC NANOPARTICLES - M. Yu. Sinitsky; E. A. Velikanova; D. K. Shishkova; A. V. Ponasenko; A. G. Kutikhin (Атеросклероз, 2018)
Aim. To study the expression of scavenger-receptor genes SCARF1 , MSR1 , CD36 , LDLR , VLDLR and cell adhesion genes VCAM1 , ICAM1 , PECAM1 , SELE , SELP , CDH5 potentially responsible for endothelial toxicity of mineral-organic nanoparticles (bions) in cultures of endothelial cells exposed to magnesium phosphate (MPB) and calcium phosphate bions (CPB). Materials and methods. In this study we used the culture of human immortalized venous endothelial cells (EA.hy 926 line), as well as commercial cultures of primary human coronary (HCAEC) and internal thoracic artery endothelial cells (HITAEC). Cells were cultured in the presence of synthesized MPB and CPB and pure phosphate-saline buffer (control). Immediately after cultivation, total RNA was isolated from samples of the cell lines. Based on the isolated RNA, a single-stranded cDNA was synthesized using a reverse transcription reaction. Evaluation of gene expression in cell cultures was carried out using Real-Time quantitative PCR with a SYBR Green fluorescent dye. Statistical analysis of the results was performed in GraphPad Prism 6 software. Results. Exposure of EA.hy 926 cells by MPB did not lead to significant changes in the expression of the studied genes except SELP and SELE compared with non-exposed control. Two-fold change in gene expression was shown for the SCARF1 and CD36 genes in culture exposed to spherical CPB (SCPB), as well as for the ICAM1 gene in culture exposed to needle-like CPB (NCPB). CPB exposure to HCAEC and HITAECcultures resulted in a pronounced decrease of expression of the CD36 and SELP genes and an increase of expression of the ICAM1 gene both in HCAEC and HITAEC.Expression of the VCAM1 and SELE genes was 2.5-fold higher in HCAEC exposed to NCPB and 2-fold increase of expression of the VLDLR gene HITAEC exposed to both types of CPB and the PECAM1 exposed to SCPB. MPB had practically no effect on the expression of the studied genes in the EA.hy 926 and HCAEC cultures, but at the same time they increased the expression of the PECAM1 gene and reduced the expression of the SELP and CDH5 genes in HITAEC. Conclusion.The chemical composition and morphology of bions, as well as the physiological characteristics of vessels can affect to gene expression signature in cultures of endothelial cells.